Digital Communication as a Tool for Improving Organizational Performance - Harjono Padmono Putro (Jurnal Info Sains : Informatika dan Sains, 2023)
In an era of ever-evolving information technology, modern organizations increasingly rely on digital communications to facilitate internal and external interactions. This research aims to investigate the role and impact of digital communication as a tool for improving organizational performance. This research uses a qualitative approach with descriptive methods. The research results show that the application of digital communication has a positive impact on organizational performance. Factors such as adequate technological infrastructure, digital literacy of organizational members, clear policies and protocols, leadership level support, appropriate communication context and objectives, and information security, contribute significantly to the success of digital communications. Research highlights benefits such as rapid exchange of information, efficient coordination, strengthening internal networks, transparency, overcoming geographic barriers, and increased engagement of organizational members. However, challenges such as security risks and information overload also need to be considered. Therefore, understanding and managing these factors is key in maximizing the role of digital communications to achieve organizational goals more effectively.